Opportunities and Challenges for Indonesian Merchants in the Serikin Market - Ayuni, Hesti Diah; Marcella, Nadya; Gea, Havizal Syahrizen; Kurniasih, Erni Panca; Rosyadi, Rosyadi (Sebatik, 2025)
Serikin Market, located on the border of Malaysia and Indonesia, is a bustling cross-border trading center with informal sector players. The market offers great opportunities for informal businesses to increase their income and expand their business, thanks to the high shopping interest of local people and tourists who are interested in Indonesian products. However, there are various challenges that informal traders face, such as limited infrastructure and supporting facilities. This study aims to identify and analyze the strengths, weaknesses, opportunities, and threats of the informal sector involved in trading at Serikin Market from Indonesia. As well as, determining the right strategy to optimize the informal sector involved in trading in Serikin Market. The research method used is descriptive qualitative analysis. Data were collected through observation, interviews, and library studies. The technique used is phenomenological analysis. The results showed that before and after the inauguration of the Jagoi Babang Cross Border Post did not change the income earned, only changes in regulation and access. Serikin Market has the power to attract traders and consumers from various countries. The strategic location, uniqueness of local products, competitive prices, and cultural appeal make Serikin Market an ideal place for traders to sell their products. It can provide great opportunities for traders, especially since many consumers from Malaysia are interested in Indonesian products, so the traders can earn a large profit. However, the main drawback faced is the lack of good market management and also faces challenges, such as limited infrastructure. The market is often not equipped with adequate facilities such as a large parking area, proper selling space, and clean public toilets.